Projeto industrial para aeração automática de leiras de compostagem orgânica - Figueira Júnior, Edson Alves (2012)
Composting is a safety environmental alternative to reuse and treat organic wastes produced by human-beings. Although decomposition naturally happens, the handling of some factors, such as oxygen level, temperature, moisture content and pH, can alter the process speed, accelerating microbial activity. Aeration is a crucial practice during the composting process, since it can ensure adequate oxygen supply, temperature control and moisture content reduction in the windrows. Therefore, this work aimed to develop an automated process of compost pile aeration in order to accelerate and optimize the production of biofertilizers in an industrial plant. The trial was carried out at Valoriza Fertilizantes Company located in the city of Uberlândia - MG. Based on previous tests done in the company s standard ventilation system an automated system of forced aeration (SAFA) was projected. After installing this system, moisture content, oxygen level and temperature tests were performed aiming to verify the efficiency of the developed aeration system.